A tomato tocopherol-binding protein sheds light on intracellular a-tocopherol metabolism in plants - Bermudez Salazar, Luisa; del Pozo, Talía; Lira, Bruno Silvestre; Godoy, Fabiana de; Boos, Irene; Romano, Cecilia; Previtali, Viola; Almeida, Juliana; Brehelin, Claire; Asis, Ramón; Quadrana, Leandro Daniel; Demarco, Diego; et al. (Oxford University Press, 2019)
Tocopherols are non-polar compounds synthesized in the plastids, which function as major antioxidants of the plant cells and are essential in the human diet. Both the intermediates and final products of the tocopherol biosynthetic pathway must cross plastid membranes to reach their sites of action. So far, no protein with tocopherol binding activity has been reported in plants. Here, we demonstrated that the tomato SlTBP protein is targeted to chloroplasts and able to bind α-tocopherol. SlTBP-knockdown tomato plants exhibited reduced levels of tocopherol in both leaves and fruits. Several tocopherol deficiency phenotypes were apparent in the transgenic lines, such as alterations in photosynthetic parameters, dramatic distortion of thylakoid membranes and significant variations in the lipid profile. These results, along with the altered expression of genes related to photosynthesis, and tetrapyrrole, lipid, isoprenoid, inositol/phosphoinositide and redox metabolism, suggest that SlTBP may act in conducting tocopherol (or its biosynthetic intermediates) between the plastid compartments and/or at the interface between chloroplast and endoplasmic reticulum membranes, affecting interorganellar lipid metabolism.